Permohonan The Philosophy of Sunni Sufism and Jurisprudence According to Muhammad Hasyim Asy'ari: The Foundations of Sharia and His Attitude towards Ibahiyah - Moh. Ali Ghafir; Abdul Kadir Riyadi; Nur Hadi Ihsan; Nasiri Nasiri; Miftahul Ulum (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2026)
During modern spiritual dynamics, a dichotomy often arises between Sharia (Islamic law) and Sufism, accompanied by the spread of Ibahiyyah a school of thought that disregards formal religious laws in pursuit of ma'rifah (gnosis). The thought of Hasyim Asy’ari serves as a theological compass that preserves the authenticity of Islamic spirituality, ensuring that it remains grounded in legal discipline (taklif). This study aims to comprehensively analyze the concept of Sunni Sufism in the primary texts of Hasyim Asy’ari, dissect his critical arguments against spiritual deviations, and identify the contributions of his thought to the sustainability of moderate Islam in Indonesia. This qualitative, descriptive-analytical study is categorized as library research. The approach utilized is a biographical study focusing on the content analysis of Hadratussyaikh Hasyim Asy'ari’s corpus of thought. Primary data were collected through close reading techniques of the texts Adab al-’Alim wa al-Muta’allim, Ad-Durar al-Muntatsirah, Risalah Ahl al-Sunnah wa al-Jama’ah, and Al-Tibyan. The analysis was conducted using textual and contextual interpretation techniques to identify the common thread between the aspects of Sharia, tariqah (the spiritual path), and haqiqah (the ultimate truth). The results of this study show that: (1) Hasyim Asy’ari’s Sufism is a manifestation of Sunni Sufism that is fully integrated with Sharia through the concept of Tariqah Tarbawiyah; he views the act of seeking knowledge (ngaji) as the primary instrument for attaining Allah's pleasure and positions authoritative texts as spiritual guides when a perfect master (mursyid kamil) is difficult to find. (2) His sharp criticism of Ibahiyyah serves as a "theological fence" to protect the authenticity of Sufism from spiritual liberalization, asserting that no matter how high a person's spiritual level is, it does not exempt them from legal obligations (taklif).